Cu2SnS3 Thin Films Deposited via Automated Spray Pyrolysis System for Solar Collectors Applications - Hadi, Zaid L.; Essa, Mohammed Sh.; Chiad, Bahaa T. (Iraqi Journal of Science, 2025)
Copper tin sulfide (CTS) thin films were deposited on glass substrates using the spray pyrolysis technique. The solution mixture was sprayed onto the glass substrate at 310°C. The CTS thin films have a monoclinic crystal structure based on XRD analysis. FTIR confirmed Cu, Sn, and S chemical bonding, whereas the Scherrer formula predicted nanoscale particle size. The AFM analysis revealed a surface roughness measurement of 42 nm. Substrates coated with CTS film showed uniformity, which revealed the coated surface shape and design. A precise measurement of the substrate temperature was made. EDX confirmed Cu-Sn-S composition. For solar collector applications, thin films deposited in CTS were treated with a blue laser source with a 405 nm wavelength.